1D ladder and 2D bilayer coordination polymers constructed from a new T-shaped ligand: luminescence, magnetic and CO2 gas adsorption properties. Issue 17 (14th April 2021) - Yin, Meng-Ru; Yan, Qing-Qing; Li, Bin; Yong, Guo-Ping
Abstract : 1D ladder and 2D bilayer coordination polymers are constructed by using a new T-shaped ligand, in which the 2D bilayer exhibits CO2 gas adsorption features. Abstract : A new three-connecting T-shaped ligand, (4-3′-pyridyl-, 6-4′-carboxylphenyl)picolinic acid (H2 L), was used to construct four coordination polymers: [Mn(L)(H2 O)2 ]·2H2 O n (1 ), [Cd(HL)(Cl)]·0.5H2 O n (2 ), [Co(L)(H2 O)] n (3 ) and [Ni(L)(H2 O)2 ]·1.5H2 O n (4 ). Based on this T-shaped ligand, one 1D ladder chain (1 ) and two unique 2D bilayers (2 and 3 ) were constructed. Regardless of the three-connecting L 2− ligand, 4 only consists of an infinite 2D network, in which two L 2− ligands bridge two Ni II centres, leading to a rhombic grid motif that is further connected to four adjacent rhombic grids, resulting in a 2D polymeric network. Interestingly, both 2 and 3 possess rhombic voids and exhibit CO2 gas adsorption features. Because coordination polymer 2 possesses a larger pore size (11.60 × 7.86 Å)/volume (16.7%) than that of 3 (11.53 × 7.65 Å/10.2%), 2 exhibits higher CO2 adsorption capacities at 273 K. Furthermore, the magnetic properties and photoluminescence have also been investigated. The present work provides a promising approach to design a new T-shaped ligand and construct various coordination polymers or metal–organic frameworks, and then to tune CO2 adsorption properties.